2001
DOI: 10.1046/j.1442-2018.2001.00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing job satisfaction and ethical dilemmas in acute psychiatric care

Abstract: This study addressed the factors that nursing staff perceived as creating job satisfaction in their working environment in addition to addressing the ethical dilemmas that staff experienced within an acute psychiatric care setting. It also addressed how clinical supervision contributed to job satisfaction among staff as well as the differences between staff who attended and staff who did not attend to clinical supervision. Data were analyzed using descriptive statistics. Overall, the results of this study show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 31 publications
2
61
0
3
Order By: Relevance
“…The instrument consisted of 29-items which were answered on a 6-point Likert scale which was anchored by the terms, 'strongly disagree' (1) and 'strongly agree' (6). The content validity, construct validity and the reliability of the WEQ had been previously established (the overall α-coefficient was 0.91) [20]. In this study, the reliability of the WEQ was 0.73.…”
Section: Methodsmentioning
confidence: 50%
See 1 more Smart Citation
“…The instrument consisted of 29-items which were answered on a 6-point Likert scale which was anchored by the terms, 'strongly disagree' (1) and 'strongly agree' (6). The content validity, construct validity and the reliability of the WEQ had been previously established (the overall α-coefficient was 0.91) [20]. In this study, the reliability of the WEQ was 0.73.…”
Section: Methodsmentioning
confidence: 50%
“…The findings from research studies which investigated what the staff perceived as creating job satisfaction in their psychosocial work environment, as well as the ethical dilemmas which were experienced within the acute psychiatric care, showed that the factors which contributed to the job satisfaction or dissatisfaction could be related to the nurses' value system [19]. The ethical dilemmas were specifically concerned with how to care for and handle the work in relation to the patient autonomy and how to approach the patient [20].…”
Section: Others Sectionmentioning
confidence: 99%
“…O conceito de QVT encerra escolhas de bem-estar e percepção do que pode ser feito para atender expectativas de gestores e trabalhadores (1) . A satisfação no trabalho tem se tornado um conceito chave dentro das pesquisas de QVT e em pesquisas da área de enfermagem em todo o mundo (2)(3)(4)(5) . Alguns estudos têm apontado a importância da mensuração da satisfação profissional e sugerido a associação da mesma com melhor qualidade de vida (6) , menor índice de estresse ocupacional, ansiedade e depressão (5,7) , com o senso de coerência (5) e menor prevalência de sintomas da Síndrome de Burnout (8)(9) .…”
Section: Introduçaounclassified
“…Unlike the ward atmosphere, with its focus on treatment and patients, the psychosocial work environment emphasizes the situation for the nursing staff, in terms of organizational conditions for their work and relational aspects among the nursing staff and between staff and managers. Previous research in psychiatric care has shown that the psychosocial work environment is vital for the staffs' job satisfaction, 18,19 and is important in relation to stress. 15,20 The psychosocial work environment has also found to be related to nurses' moral sensitivity, 21 and low staffing levels have shown to be associated with moral distress among Japanese psychiatric nurses.…”
Section: Introductionmentioning
confidence: 99%